2017
DOI: 10.34019/2596-3325.2017.v18.24689
|View full text |Cite
|
Sign up to set email alerts
|

Dieta de morcegos insetívoros (Mammalia: Chiroptera) em fragmentos de Floresta de Araucárias, no Sul do Brasil

Abstract: Acredita-se que morcegos insetívoros de crânio robusto consumam uma maior variedade de insetos, enquanto os de crânio delicado consumam em sua maioria insetos mais "macios". Assim, o presente estudo analisou a dieta de morcegos insetívoros de crânios robustos e delicados. As análises foram feitas a partir de amostras fecais obtidas de espécimes capturados em dois fragmentos de Floresta de Araucárias no Sul do Brasil. Os fragmentos de insetos registrados foram identificados até o nível de Ordem. Foram calculada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Patterns of cave occupancy and preference have emerged from studies in limestone and sandstone karst areas, including sets of caves and isolated ones, carried out in the 1980-90s and situated in different phytogeographic domains: Atlantic forest -Alto Ribeira/SP (Arnone 2008;Trajano 1985), Corumbataí/SP (Campanhã and Fowler 1993), Rio Pardo/BA (Santos 2001); Cerrado -Distrito Federal (Bredt et al 1999) and Mambaí/GO (Ésberard et al 2001); Amazon Forest -Altamira-Itaituba/PA (Trajano and Moreira 1989); and isolated caves in different biomes (Gregorin and Mendes 1999;Silva et al 2001;Trajano and Gimenez 1998;Uieda et al 1980;). These patterns were corroborated by studies in the last decades in various biomes, mostly Caatinga (semiarid dry forest) and Cerrado (e.g., Bichuette et al 2018;Cajaiba 2014;Cajaiba et al 2021;Esbérard et al 2005;Felix et al 2016;Guimarães and Ferreira 2014;Otálora-Ardila et al 2019;Portella 2010;Schmaedecke et al 2019;Silva et al 2009;Zortéa et al 2015;). We present a summary of these data.…”
Section: Diversity Of Lithophilous Bats In Brazilmentioning
confidence: 57%
“…Patterns of cave occupancy and preference have emerged from studies in limestone and sandstone karst areas, including sets of caves and isolated ones, carried out in the 1980-90s and situated in different phytogeographic domains: Atlantic forest -Alto Ribeira/SP (Arnone 2008;Trajano 1985), Corumbataí/SP (Campanhã and Fowler 1993), Rio Pardo/BA (Santos 2001); Cerrado -Distrito Federal (Bredt et al 1999) and Mambaí/GO (Ésberard et al 2001); Amazon Forest -Altamira-Itaituba/PA (Trajano and Moreira 1989); and isolated caves in different biomes (Gregorin and Mendes 1999;Silva et al 2001;Trajano and Gimenez 1998;Uieda et al 1980;). These patterns were corroborated by studies in the last decades in various biomes, mostly Caatinga (semiarid dry forest) and Cerrado (e.g., Bichuette et al 2018;Cajaiba 2014;Cajaiba et al 2021;Esbérard et al 2005;Felix et al 2016;Guimarães and Ferreira 2014;Otálora-Ardila et al 2019;Portella 2010;Schmaedecke et al 2019;Silva et al 2009;Zortéa et al 2015;). We present a summary of these data.…”
Section: Diversity Of Lithophilous Bats In Brazilmentioning
confidence: 57%
“…Bats present different foraging strategies, for example, vespertilionids and emballonurids obtain most of their food in mid-flight, capturing insects up to the approximate height of the treetops, whereas molossids generally perform their foraging above this stratum (Reis et al 2007). How these animals perform the foraging and the types of habitats occupied can indicate, in a considerable way, the composition of the diet (Emiliano et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They are large bats, with a body mass from 21 to 43 g and forearms from 46 to 53 mm long (Gregorin & Taddei 2002, Reis et al 2017. Food habit records include orders such as Coleoptera, Hymenoptera, Hemiptera, Orthoptera, Lepidoptera, Diptera, Odonata (Fenton et al 1998, Freeman 1981, Marques 1986, Howell & Bruch 1974, Pine 1969, and for southern Brazil, Emiliano et al (2017) reported high consumption of Coleoptera and Lepidoptera by Molossus spp.…”
Section: Introductionmentioning
confidence: 99%
“…velatus is a species with an average body size of 62 mm, forearm between 42 and 50 mm, and body weight of 11 grams (Reis et al, 2013). They are insectivorous animals (Emiliano et al, 2017), and reinforces the importance of ecosystem services, given that bats from this trophic guild can especially suppress and control insect biomass (Moiseienko and Vlaschenko, 2021). However, there are few works available on ecology, behavior and interspecific associations, and exploration of refuges that refer to H. velatus.…”
Section: Introductionmentioning
confidence: 99%